The Role, Functions and Tasks of the Press Service in Public Institutions (Zien Journal of Social Sciences and Humanities, 2022)
The purpose of the article is to consider the specifics of the role of the press service in creating a harmonious relationship between the public and state bodies. Special attention is paid to the study of the functions, tasks and resolutions of the President of the Republic of Uzbekistan Sh.Mirziyoyev "On the most important measures to ensure the independence of the mass media and the development of the activities of the press services of state bodies and organizations " in general